PENGEMBANGAN MEDIA SMART BOX PADA MATERI PENERAPAN NILAI-NILAI PANCASILA DALAM KEHIDUPAN SEHARI-HARI DI KELAS V SEKOLAH DASAR - Saluni, Mila; Pomalingo, Samsi; Ismail, Reska Putri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to develop Smart Box learning media that meets the criteria of feasibility, practicality, and effectiveness in Civics learning to improve student learning outcomes in the material on the Application of Pancasila Values ​​in Daily Life. This study uses the (Research and Development) method using the ADDIE development research model, which includes the stages of analyze, design, development, Implement, and Evaluate. The feasibility of the Smart Box media was tested through validation by a team of experts. The results of the media validation obtained a score of 95, including the